Incompressible Limit of Nonisentropic Ideal Magnetohydrodynamic Flows with General Initial Data (Journal of Partial Differential Equations, 2025)
The incompressible limit of nonisentropic ideal magnetohydrodynamic equations with general initial data in the whole space $\mathbb{R}^3$ is proved in this paper. The uniform estimates of solutions with respect to the Mach number are obtained by usingenergy estimate. Strong convergence results of the smooth solutions are establishedby using Strichartz’s estimates in the whole space.
Keywords: Incompressible limit; general initial data; nonisentropic MHD equations.